Intranodal lymphangiography combined with foam sclerotherapy embolization of thoracic duct in the treatment of postoperative chylous leakage for thyroid carcinoma: a case report and review - Liu, RuiJiang; Cao, Lei; Du, JingXin; Xie, Ping (Frontiers in Radiology, 2024)
Chylous leakage (CL) is a rare but significant complication following cervical lymph node dissection, particularly in patients with papillary thyroid carcinoma (PTC). This condition is characterized by the leakage of lymphatic fluid, which can result in severe consequences such as malnutrition, immunosuppression, and prolonged hospital stays. Conventional treatments for CL include conservative measures and surgical interventions, but these approaches often face limitations and challenges. This case report discusses a successful treatment of CL using thoracic duct lymphangiography combined with local injection of sclerotherapy, demonstrating a novel and effective approach for managing this complication.